1999
DOI: 10.1161/01.cir.100.21.2153
|View full text |Cite
|
Sign up to set email alerts
|

Opening and Closing Characteristics of the Aortic Valve After Different Types of Valve-Preserving Surgery

Abstract: Near-normal opening and closing characteristics can be achieved by a technique that preserves the shape and independent mobility of the sinuses of Valsalva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(197 citation statements)
references
References 20 publications
11
177
2
7
Order By: Relevance
“…Although vortices cannot be visualized in the sinuses of Valsalva 20) and valve opening and closing dynamics are abnormally high in postoperative patients with negligible sinuses, near-normal valve opening and closing characteristics can be achieved by creating a sinus bulge. 21,22) Finite element analyses have demonstrated similar findings. 23,24) Many devices can create pseudosinuses.…”
Section: Various Vsrr Techniquesmentioning
confidence: 55%
“…Although vortices cannot be visualized in the sinuses of Valsalva 20) and valve opening and closing dynamics are abnormally high in postoperative patients with negligible sinuses, near-normal valve opening and closing characteristics can be achieved by creating a sinus bulge. 21,22) Finite element analyses have demonstrated similar findings. 23,24) Many devices can create pseudosinuses.…”
Section: Various Vsrr Techniquesmentioning
confidence: 55%
“…Previous echocardiographic study showed that the presence of sinuses of Valsalva is important for normal cusp motion and reduction of cusp stress. 33 Similarly, CMR using time-resolved 3-dimensional phase contrast imaging showed that using an anatomically correct Dacron graft with three aortic sinuses generated flow vortices similar to normal volunteers. 34 However, patients with a repairable BAV and a dilated aortic annulus (≥28 mm diameter) often do not do well with a simple subcommissural annuloplasty.…”
Section: Thoracic Aortic Aneurysm Repairmentioning
confidence: 94%
“…At that time, the cusp's free edge area exceeded the commissural area by +16.3 ± 2.0%. This behavior of the valve cusps might explain cases of early cusp deterioration following re-implantation of the aortic valve within a tubular conduit without sinuses of Valsalva (Gallo et al, 1995;Grande-Allen et al, 2000;Leyh et al, 1999) because cusp expansion beyond the commissural level would result in cusp impact against the wall of the cylindrical conduit. Furthermore, as previously published, aortic root expansion is also asymmetric, and it induces a tilting dynamic of the aortic valve throughout the cardiac cycle (Dagum et al, 1999;Lansac et al, 2005b).…”
Section: The Ascending Aorta: a Dynamic Structurementioning
confidence: 99%